A Study of Spontaneous Imbibition Recovery Mechanism of Surfactant Formulated from Methyl Ester Sulfonates - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2013)
MES (Methyl Ester Suffocates) can be formulated to become surfactant-MES that has surfactant potential properties for EOR (enhanced oil recovery). A such formulated surfactant MES by adding some solvents and chemicals to adjust its properties in order to generate a compatibity with reservoir fluid and rock has been developed. This formulated surfactant MES, therefore, has been tested its properties for enhanced oil recovery in a selected oil field. The oil field produces an oil withc39.45oAPI, and brine content of about 18,900 mg/L equivalent NaCl concentration. While reservoir rock is not available and substituted by Bentheimer standard core. Basically the production enhancements of surfactant solution for EOR processes are wettability alteration and interfacial tension reduction. In these experiments, some evaluations have been done to observe the capability the formulated surfactant MES for oil production enhancements includingwettability alteration and imbibition capability. Formulated low interfacial tension surfactant-MES that will be evaluated for spontaneous imbibition ability have been diluted in the brine of 0.5 and 1.0% concentrations. Tests on wettability alteration indicated that the surfactant solutions could not change the wettability of the rocks. The initial wettability is mixed wet and still mixed wet after ageing in the surfactant solution. On other hand the spontaneous imbibition tests resulted in significant oil production coming out from the cores, i.e. 67.07% oil recovery with 0.5% surfactant and 92.25% for 1.0% surfactant solutions. But optimum oil recovery factor by brine imbibition is only 41.69%